Understanding resilience factors among high-risk groups amidst the COVID-19 endemic in Malacca - Low, Choon Yu; Loh, Yoke Ling; Kamaruzzaman Abdul Manan,; Josry Sakian, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study examines the factors influencing resilience among high-risk groups in Malacca, Malaysia, during the COVID-19 endemic. High-risk groups, such as the elderly and frontline workers, face unique challenges and vulnerabilities during the public health crisis, which has brought about significant socio-economic disruptions, psychological distress, and uncertainty. The residents of Malacca have been significantly affected by the endemic, potentially leading to diminished resilience among the population. The study aims to measure the levels of knowledge, family support, media exposure, optimistic thinking, and resilience regarding COVID-19 prevention among the at-risk groups in Malacca. Secondly, it aims to assess the relationships between knowledge, family support, media exposure, optimistic thinking, and resilience within this population. Thirdly, it seeks to identify the best predictor of resilience among these high-risk groups. A quantitative research design was employed to achieve these objectives. A total of 384 respondents participated in an online survey, revealing that optimistic thinking significantly contributed to increasing resilience levels, particularly among those anxious about their safety. Optimistic thinking also positively impacted coping abilities. However, family support and media exposure did not show significant associations with resilience. Developing holistic support systems that consider all factors affecting resilience, including knowledge, family support, media exposure, and optimistic thinking, is essential for high-risk groups in Malacca. This study offers valuable insights into the factors influencing resilience among high-risk groups in Malacca during the COVID-19 endemic. Integrating these findings into public health and social welfare initiatives can create a comprehensive approach to supporting vulnerable individuals during challenging times.